Method for preparing an anode for lithium-ion batteries

CN117239066BActive Publication Date: 2026-11-03TSINGHUA UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210656097.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-10
Publication Date
2026-11-03
Estimated Expiration
2042-06-10

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve uniform composite of carbon nanotubes and nano-silicon, resulting in poor flexibility and conductivity of lithium-ion battery anodes, and the nano-silicon is prone to agglomeration, which affects battery performance.

Method used

By coating the surface of nano-silicon with a positively charged carbonizable polymer, such as polyaniline, carbon nanotubes and nano-silicon are uniformly dispersed to form a three-dimensional network structure through electrostatic repulsion and attraction. The carbonization at high temperature forms amorphous carbon, which enhances the bonding force.

Benefits of technology

The uniform composite of carbon nanotubes and nano-silicon was achieved, which improved the mechanical strength and conductivity of the lithium-ion battery anode, enhanced the cycle stability and flexibility of the battery, and reduced the agglomeration of nano-silicon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117239066B_ABST
    Figure CN117239066B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a lithium ion battery anode, which comprises the following steps: step S1: providing a nano-silicon material, and coating a positively charged carbonizable polymer on the surface of the nano-silicon material; step S2: providing a solvent and carbon nanotubes, adding the carbon nanotubes and the nano-silicon with the surface coated with the positively charged carbonizable polymer obtained in step S1 into the solvent in a certain proportion, and performing ultrasonic dispersion to obtain a dispersion liquid; and step S3: performing vacuum suction filtration on the dispersion liquid to obtain a composite film of CNT and the nano-silicon with the surface coated with the positively charged carbonizable polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, and more particularly to a method for preparing a lithium-ion battery anode based on nano-silicon and carbon nanotubes. Background Technology

[0002] Silicon, with its extremely high theoretical specific capacity and abundant reserves, is an ideal anode material. In recent years, the rapid development of electronic devices has placed new demands on their flexibility, making the fabrication of flexible silicon anodes crucial. However, the severe volume changes in silicon during lithium-ion battery cycling can easily lead to electrode breakage and separation from the current collector; moreover, silicon's poor flexibility and conductivity further limit its application in lithium-ion batteries. Compared to conventional silicon, nano-silicon can better withstand the mechanical stress caused by volume changes, effectively preventing particle breakage; moreover, its nanoscale size shortens the electron transport path and improves its conductivity. However, nano-silicon is more prone to agglomeration.

[0003] Carbon nanotubes (CNTs) possess properties such as high aspect ratio, clean surface, strong van der Waals forces, and excellent mechanical, electrical, and thermal properties. Macroscopic materials prepared from CNTs, such as carbon nanotube films and carbon nanotube sponges, exhibit excellent electrothermal and mechanical flexibility. Therefore, by combining CNTs with nano-silicon, flexible nano-silicon anodes with good electrical conductivity can be obtained.

[0004] However, both CNTs and silicon nanoparticles have negative zeta potentials, leading to mutual repulsion due to electrostatic interactions. Existing lithium-ion anode fabrication methods struggle to achieve uniform composites of CNTs and silicon nanoparticles, thus hindering the production of uniform anodes for lithium-ion batteries. Summary of the Invention

[0005] In view of this, it is indeed necessary to provide a method for preparing a flexible nano-silicon lithium-ion battery anode, in which the CNTs and nano-silicon in the flexible nano-silicon lithium-ion battery anode obtained by the preparation method are uniformly combined and the nano-silicon does not agglomerate.

[0006] A method for preparing a lithium-ion battery anode includes the following steps:

[0007] Step S1: Provide a nano-silicon material and coat the surface of the nano-silicon material with a positively charged carbonizable polymer to obtain nano-silicon with a positively charged polymer coating.

[0008] Step S2: Provide a solvent and carbon nanotubes, add the carbon nanotubes and the nano-silicon coated with a positively charged polymer to the solvent in a certain proportion, and perform ultrasonic dispersion to obtain a dispersion; and

[0009] Step S3: Vacuum filter the dispersion to obtain a composite membrane of CNTs and nano-silicon coated with a positively charged carbonizable polymer.

[0010] Compared to existing technologies, the method for preparing the lithium-ion battery anode provided by this invention involves coating a positively charged carbonizable polymer onto the surface of nano-silicon. Because the surface of the nano-silicon is coated with this positively charged carbonizable polymer, and the zeta potential of the carbon nanotubes is negative, the carbon nanotubes and the positively charged carbonizable polymer are heterogeneously charged. The nano-silicon modified by the carbon nanotubes and the positively charged carbonizable polymer can be "dispersed" through their respective electrostatic repulsion and "anchored" through mutual electrostatic attraction. Therefore, the nano-silicon coated with the positively charged carbonizable polymer is uniformly dispersed within the three-dimensional network structure formed by the carbon nanotubes and can be well integrated with them. This continuous three-dimensional network structure can simultaneously serve as a mechanical support framework and a transport grid for electrons and lithium ions. Attached Figure Description

[0011] Figure 1 A flowchart illustrating a method for preparing a lithium-ion battery anode according to an embodiment of the present invention.

[0012] Figure 2 The simulation diagram shows the dispersion between silicon nanotubes and carbon nanotubes, as well as the dispersion simulation diagram between silicon nanotubes (SiPA) and carbon nanotubes coated with polyaniline.

[0013] Figure 3 This is a schematic diagram illustrating the preparation process of CNT@Si composite film and CNT@SiPA composite film provided in the embodiments of the present invention.

[0014] Figure 4 This is a schematic diagram of carbon nanotube functional layers laid on two surfaces of a composite membrane, as provided in an embodiment of the present invention.

[0015] Figure 5 A scanning electron microscope (SEM) image of a cross-section of a lithium-ion battery anode obtained by the preparation method provided in this embodiment of the invention.

[0016] Figure 6 SiPA provided for embodiments of the present invention 0.01 SiPA 0.005 and SiPA 0.015 Thermogravimetric analysis (TGA) curves.

[0017] Figure 7 Cycle performance diagrams of button cells assembled with CNT@Si, CNT@Si-film, CNT@SiPAC, and CNT@SiPAC-film anodes, respectively, provided in embodiments of the present invention.

[0018] Figure 8 To adopt the CNT@SiPAC in Examples 1-30.01 - Membrane, CNT@SiPAC 0.005 - Membrane and CNT@SiPAC 0.015 - Cycle performance diagram of coin cells obtained from membrane anodes.

[0019] Figure 9 In the CNT@SiPAC-film anode of this embodiment of the invention, the areal loading of Si is 1.19 mg / cm³. -2 1.38mg cm -2 1.72mg cm -2 and 1.99mg cm -2 The cycle capacity curve of the battery at that time.

[0020] Figure 10 The rate performance curves of the battery composed of CNT@Si, CNT@Si-film, CNT@SiPAC, and CNT@SiPAC-film anodes provided in the embodiments of the present invention are shown.

[0021] Figure 11 The diagram shows the cycle performance of the SiPAC / / Li pouch cell provided in an embodiment of the present invention.

[0022] Figure 12 The resistance of the Si slurry electrode and CNT@SiPAC-film electrode provided in the embodiments of the present invention changes with the number of bending cycles when subjected to long cyclic bending at 90° and 180°.

[0023] Figure 13 The voltage curves of the SiPAC / / LFP soft-pack battery before and after bending are provided in an embodiment of the present invention.

[0024] Figure 14 This is a schematic diagram of the structure of a lithium-ion battery anode provided in an embodiment of the present invention.

[0025] Figure 15 This is a schematic diagram of the structure of a lithium-ion battery anode provided in another embodiment of the present invention.

[0026] Explanation of main component symbols

[0027] Lithium-ion battery anode 100, 200

[0028] Three-dimensional network structure of carbon nanotubes 102, 202

[0029] 104 nano-silicon particles coated with amorphous carbon

[0030] Carbon nanotube functional layer 106

[0031] 204 nano-silicon particles coated with positively charged carbonizable polymer

[0032] The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation

[0033] The embodiments of this technical solution will be further described in detail below with reference to the accompanying drawings and specific examples.

[0034] Please see Figure 1 The first embodiment of the present invention provides a method for preparing a lithium-ion battery anode, comprising the following steps:

[0035] Step S1: Provide a nano-silicon material and coat the surface of the nano-silicon material with a positively charged carbonizable polymer to obtain nano-silicon coated with a positively charged carbonizable polymer.

[0036] Step S2: Provide a solvent and carbon nanotubes (CNTs), add the carbon nanotubes and the nano-silicon coated with a positively charged carbonizable polymer to the solvent in a certain proportion, and perform ultrasonic dispersion to obtain a dispersion.

[0037] Step S3: Vacuum filter the dispersion to obtain a composite film of CNTs and nano-silicon coated with a positively charged carbonizable polymer.

[0038] Step S4: Deposit a carbon nanotube functional layer on each of the two opposite surfaces of the composite membrane, such that the composite membrane is located between the two carbon nanotube functional layers. Each carbon nanotube functional layer comprises at least two super-aligned carbon nanotube membranes stacked together.

[0039] Step S5: The composite film with carbon nanotube functional layers laid in step S4 is subjected to high-temperature calcination, so that the positively charged carbonizable polymer in the composite film is carbonized into amorphous carbon.

[0040] In step S1, the positively charged carbonizable polymer refers to a polymer with a positive surface zeta potential, which can decompose into amorphous carbon during high-temperature calcination. For example, the positively charged carbonizable polymer can be polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0041] In the nano-silicon coated with a positively charged carbonizable polymer, the mass percentage of nano-silicon is preferably 40%-50%. In this embodiment, the positively charged carbonizable polymer is polyaniline, and the mass percentage of nano-silicon in the polyaniline-coated nano-silicon is 45.5%.

[0042] The coating method for the surface of the nano-silicon material with a positively charged carbonizable polymer can be selected based on the specific substance of the positively charged carbonizable polymer. In this embodiment, aniline, hydrochloric acid, ammonium persulfate, and other materials are used to perform in-situ polyaniline coating on the nano-silicon in an ice-water mixed bath to obtain nano-silicon (SiPA) with a polyaniline-coated surface.

[0043] In this embodiment, the size of the silicon nanoparticles is 20 nanometers to 80 nanometers. Of course, the size of the silicon nanoparticles is not limited to the size in this embodiment, and can also be silicon nanoparticles of other sizes.

[0044] In step S2, the solvent is a solvent capable of dispersing carbon nanotubes and nano-silicon coated with a positively charged carbonizable polymer, such as ethanol, acetone, or water. In this embodiment, the solvent is ethanol.

[0045] The carbon nanotubes can be directly scraped from a super-aligned carbon nanotube array into the solvent. The super-aligned carbon nanotube array is preferably disposed on a substrate and can be scraped off the substrate using a blade or other tools. The carbon nanotubes in the super-aligned carbon nanotube array generally have a length greater than or equal to 300 micrometers and a diameter less than or equal to 30 nanometers, and the carbon nanotubes are arranged in a basically consistent direction. The surfaces of the carbon nanotubes in the super-aligned carbon nanotube array are pure and basically free of impurities, such as amorphous carbon or residual catalyst metal particles.

[0046] The preferred loading of silicon nanoparticles in the nano-silicon coated with a positively charged carbonizable polymer is 1-5 mg / cm³. -2 If the loading is too low, the silicon anode capacity will be too small; if the loading is too high, the silicon anode volume will change significantly and pulverization will be severe, resulting in poor capacity retention. The loading within this preferred range can balance anode capacity and capacity retention. In this embodiment, the loading of nano-silicon in the surface-coated polyaniline-coated nano-silicon is 3 mg / cm³. -2 .

[0047] The preferred mass ratio of carbon nanotubes to nano-silicon coated with a positively charged carbonizable polymer is 1:2 to 1:4. In this embodiment, the mass ratio of carbon nanotubes to nano-silicon coated with polyaniline is 1:3.

[0048] In this embodiment, a cell ultrasonic pulverizer is used for the above-mentioned ultrasonic dispersion. Of course, other ultrasonic devices can also be used for ultrasonic dispersion, and it is not limited to the cell ultrasonic pulverizer in this embodiment.

[0049] The ultrasonic dispersion time can be set according to actual needs. For example, the size of the super-aligned carbon nanotube array and the ultrasonic dispersion power will affect the ultrasonic dispersion time. Ultrasonic dispersion can be stopped after the carbon nanotubes form a three-dimensional network structure in the solvent. The three-dimensional network structure is a flocculent structure. This flocculent structure is not merely the intertwining of carbon nanotubes, but also a porous and fluffy structure. After ultrasonic dispersion, the carbon nanotubes in the solvent form a continuous three-dimensional network structure, and the carbon nanotubes in this continuous three-dimensional network structure are uniformly distributed. Because the surface of the nano-silicon is coated with a positively charged carbonizable polymer, the zeta potential of the carbon nanotubes is negative. The carbon nanotubes and the positively charged carbonizable polymer are heterocharged. The carbon nanotubes and the positively charged carbonizable polymer-modified nano-silicon can be "dispersed" by their respective electrostatic repulsion and "anchored" by mutual electrostatic attraction. Therefore, the nano-silicon coated with a positively charged carbonizable polymer is uniformly dispersed in the three-dimensional network structure formed by the carbon nanotubes and can be well combined with the carbon nanotubes. This continuous three-dimensional network structure can simultaneously serve as a mechanical support framework and a transport grid for electrons and lithium ions.

[0050] Please see Figure 2 The dispersion between silicon nanotubes (Si) and carbon nanotubes scraped from a SACNT array was simulated, as was the dispersion between silicon nanotubes (SiPA) coated with polyaniline and carbon nanotubes scraped from a SACNT array. Figure 2 As can be seen, before coating with polyaniline, in the potential range from -3.9 mV (Si) to 0 mV (boundary), Si is driven away from CNTs by electrostatic repulsion over 50 ns. In the potential range from -1.6 mV (CNT) to 6.4 mV (SiPA), SiPA approaches CNTs by electrostatic attraction over 20 ns. Simulation results show that Si and CNTs with the same charge repel each other, while SiPA and SACNTs with different charges attract each other, proving the effectiveness of the "dispersion anchoring" strategy.

[0051] In step S3, after vacuum filtration, the resulting composite film of CNTs and nano-silicon coated with a positively charged carbonizable polymer forms a flexible, self-supporting material. The three-dimensional network structure formed by carbon nanotubes serves as a mechanical support framework, and the nano-silicon coated with a positively charged carbonizable polymer is uniformly dispersed within the three-dimensional network structure.

[0052] Composite membranes of different sizes and shapes can be obtained by changing the size and shape of the filter membrane. Since the surface of nano-silicon is coated with a positively charged carbonizable polymer, and carbon nanotubes have a negative zeta potential, the carbon nanotubes and the positively charged carbonizable polymer are heterogeneously charged. The nano-silicon modified by the carbon nanotubes and the positively charged carbonizable polymer can be "dispersed" by their respective electrostatic repulsion and "anchored" by mutual electrostatic attraction. Therefore, the nanotubes are dispersed from each other, and the carbon nanotubes and the positively charged carbonizable polymer attract each other to form a uniform composite film.

[0053] Please see Figure 3 This is a schematic diagram illustrating the preparation process of CNT@Si composite films and CNT@SiPA composite films. Figure 3 It can be seen that in the CNT@Si composite film, the silicon nanotubes and carbon nanotubes are not combined and are separate, and the aggregation of silicon nanotubes is quite serious; while in the CNT@SiPA composite film, the silicon nanotubes and carbon nanotubes are well combined on the surface of the carbon nanotubes, and there is no aggregation between the nanotubes, and the dispersion is more uniform.

[0054] In step S4, preferably, in the at least two super-aligned carbon nanotube films stacked together, the carbon nanotubes in adjacent super-aligned carbon nanotube films are arranged in an interlaced manner. The interlacing angle of the carbon nanotubes in adjacent super-aligned carbon nanotube films is not limited. In this embodiment, the interlacing angle of the carbon nanotubes in adjacent super-aligned carbon nanotube films is 90 degrees.

[0055] The fabrication process of the carbon nanotube functional layer specifically includes:

[0056] A continuous first super-aligned carbon nanotube film is extracted from a super-aligned carbon nanotube array using a stretching device and deposited onto a substrate; in this embodiment, the stretching device is a glass rod and the substrate is a metal frame.

[0057] The substrate is rotated by a certain angle, and a continuous second super-compliant carbon nanotube film is extracted from the super-compliant carbon nanotube array and deposited on the surface of the first super-compliant carbon nanotube film; in this embodiment, the metal frame is rotated by 90 degrees.

[0058] When the carbon nanotube functional layer comprises three or more super-aligned carbon nanotube film layers stacked and interleaved, the above operation is repeated multiple times to obtain the carbon nanotube functional layer. In this embodiment, the above steps are repeated 10 times, and the resulting carbon nanotube functional layer comprises 10 super-aligned carbon nanotube film layers stacked and interleaved.

[0059] The carbon nanotube functional layer can be first deposited on a substrate, and then the entire carbon nanotube functional layer on the substrate can be deposited onto both surfaces of the composite membrane. Please refer to [link / reference]. Figure 4In some embodiments, the super-aligned carbon nanotubes are pulled from the array and directly laid onto the two surfaces of the composite membrane. After laying one layer of super-aligned carbon nanotube membrane, the composite membrane is rotated to allow the super-aligned carbon nanotubes in the carbon nanotube functional layer to be stacked and interleaved.

[0060] The super-aligned carbon nanotube array consists of multiple carbon nanotubes that are substantially parallel to each other and perpendicular to the surface of the substrate. The array is essentially free of impurities, such as amorphous carbon or residual catalyst metal particles. The super-aligned carbon nanotube array is prepared using chemical vapor deposition. The preparation method for the super-aligned carbon nanotube array can be found in Chinese Patent Application Publication No. 02134760.3.

[0061] The super-aligned carbon nanotube membrane is composed of several carbon nanotubes. These carbon nanotubes are preferentially oriented in essentially the same direction, meaning that the overall extension direction of most carbon nanotubes in the super-aligned carbon nanotube membrane is essentially the same. Furthermore, the overall extension direction of most carbon nanotubes is essentially parallel to the surface of the super-aligned carbon nanotube membrane. Of course, a few randomly arranged carbon nanotubes exist in the super-aligned carbon nanotube membrane, but these do not significantly affect the overall orientation of the majority of carbon nanotubes in the membrane. Specifically, the majority of carbon nanotubes extending in essentially the same direction in the super-aligned carbon nanotube membrane are not perfectly straight; they can be appropriately curved. Or they are not arranged exactly according to the extension direction; they can be appropriately deviated from the extension direction. Therefore, it cannot be ruled out that there may be partial contact between parallel carbon nanotubes in the majority of carbon nanotubes extending in essentially the same direction in the super-aligned carbon nanotube membrane.

[0062] The number of super-aligned carbon nanotube films in the carbon nanotube functional layers on the two opposite surfaces of the composite membrane can be equal or unequal. In this embodiment, the number of super-aligned carbon nanotube films in the carbon nanotube functional layers on the two opposite surfaces of the composite membrane is equal.

[0063] In step S5, the composite membrane is calcined at high temperature for a period of time, causing the positively charged carbonizable polymer in the composite membrane to carbonize into amorphous carbon, thereby improving the conductivity of the composite membrane. The calcination temperature is selected based on the pyrolysis temperature of the positively charged carbonizable polymer. In this embodiment, the positively charged carbonizable polymer is polyaniline, which is calcined at 900°C for 3 hours.

[0064] The preferred mass loading of nano-silicon in the composite material obtained after high-temperature calcination is 1.2 mg / cm³. -2 Up to 2mg cm -2 .

[0065] Please see Figure 5 This is a scanning electron microscope (SEM) image of a cross-section of the lithium-ion battery anode obtained by the preparation method in this embodiment. Figure 5 It can be seen that the surface of the lithium-ion battery anode is covered with a carbon nanotube functional layer and the surface is clean, further proving that the high-temperature calcination process in the above preparation method will not damage the carbon nanotube functional layer.

[0066] It is understood that steps S4 and S5 are not mandatory. In some embodiments, the method for preparing the lithium-ion battery anode does not include steps S4 and S5. In other embodiments, the method for preparing the lithium-ion battery anode includes only one of steps S4 or S5. These embodiments are all within the scope of protection of this invention.

[0067] The following are the specific steps for preparing the lithium-ion battery anode and the performance tests performed on the lithium-ion battery anode in a specific embodiment of the present invention.

[0068] Example 1:

[0069] Preparation of surface-grafted amino-containing nano-silicon powder (Si-NH2):

[0070] Preparation of Solution A: Mix 1.5 g of 20-80 nm diameter silicon nanoparticles with 250 ml of ethanol and ultrasonically disperse for 20 minutes. Preparation of Solution B: Mix 15 ml of 14.5 mol / L ammonia solution with 75 ml of deionized water. Slowly add Solution B to Solution A and magnetically stir the mixture for 30 minutes. Add 2.375 g of (3-aminopropyl)triethoxysilane (APTES) dropwise to the mixture and stir for 2 hours. Collect the complex by centrifugation, wash several times with ethanol, and dry the precipitate overnight at 50 °C. Collect and grind to obtain amino-grafted silicon nanoparticles (Si-NH2).

[0071] Preparation of silicon nanoparticles (SiPA) coated with polyaniline:

[0072] Preparation of Solution C: Mix 1.4 g Si-NH2 and 200 ml ethanol, sonicate for 15 min, then add 0.01 mol aniline and continue sonicating for 30 min. Preparation of Solution D: Dissolve 5.6 g ammonium persulfate in 40 ml of 1.4 mol / L hydrochloric acid. Slowly add Solution D to Solution C at 0 °C. Maintain magnetic stirring at 0 °C for 4 hours to achieve in-situ coating of polyaniline on the Si-NH2 surface. Wash the mixture several times by centrifugation, dry the collected precipitate overnight at 50 °C, and grind to obtain SiPA.

[0073] High-temperature calcination forms amorphous carbon-coated nano-silicon (SiPAC):

[0074] SiPA was heated in a tube furnace under an argon atmosphere and held at 900°C for 3 hours to obtain amorphous carbon-coated nano-silicon (SiPAC) after PANI pyrolysis.

[0075] Preparation of CNT@Si, CNT@Si-films, CNT@SiPA, CNT@SiPA-films, CNT@SiPAC, and CNT@SiPAC-films, where @ represents the composite of two substances:

[0076] SACNT arrays were prepared by chemical vapor deposition, using iron as a catalyst and acetylene as a precursor. The CNTs in the SACNT array had a diameter of 30 nm and a height of 300 μm. The clean walls and strong van der Waals forces of the CNTs in the SACNT array allowed for the extraction of continuous supercillated CNT films from the SACNT array via an end-to-end connection mechanism.

[0077] 30 mg of Si, 10 mg of CNTs scraped from the SACNT array, and 60 ml of ethanol were mixed and sonicated for 30 minutes. The mixture was then vacuum filtered to obtain a CNT@Si composite material. Ten vertically cross-laminated SACNT films were then deposited on each surface of the CNT@Si to obtain a CNT@Si film. The mass loading of Si in both the CNT@Si and CNT@Si films was approximately 3 mg / cm³. -2 .

[0078] Using the same steps described above, CNT@SiPA was obtained by scraping 30 mg of SiPA and 10 mg of CNTs from a SACNT array. Ten layers of vertically cross-laminated SACNT films were then deposited on each of the two surfaces of the CNT@SiPA to obtain CNT@SiPA-films. The CNT@SiPA and CNT@SiPA-films were calcined (using the same calcination steps as for SiPAC preparation) to obtain CNT@SiPAC and CNT@SiPAC-films, with a Si mass loading of 1.2 mg cm⁻¹. -2 Up to 2mg cm -2 .

[0079] The SiPA prepared in Example 1 is defined as SiPA. 0.01 SiPAC is defined as SiPAC 0.01 CNT@SiPAC is defined as CNT@SiPAC 0.01 .

[0080] Example 2:

[0081] This embodiment is basically the same as Example 1, except that: 0.005 mol aniline was used to coat different amounts of PANI onto Si-NH2 to prepare SiPA. 0.005 .

[0082] SiPA 0.005 SiPAC was obtained by heat treatment using the same method as in Example 1. 0.005 CNT@SiPA was obtained using the same method as in Example 1. 0.005 and CNT@SiPA 0.005 -membrane.

[0083] Example 3:

[0084] This embodiment is basically the same as Example 1, except that: 0.015 mol aniline was used to coat different amounts of PANI onto Si-NH2 to prepare SiPA. 0.015 .

[0085] SiPA 0.015 SiPAC was obtained by heat treatment using the same method as in Example 1. 0.015 CNT@SiPA was obtained using the same method as in Example 1. 0.015 and CNT@SiPA 0.015 -membrane.

[0086] Please see Figure 6 SiPA in Examples 1-3 0.01 SiPA 0.005 and SiPA 0.015 The mass percentages of medium- and nano-sized Si were 45.5%, 51.1%, and 39.4%, respectively.

[0087] Comparative Example 1

[0088] Preparation of Si-slurry electrodes

[0089] Nano-Si, conductive carbon black, and CMC were mixed in water at a weight ratio of 8:1:1 and coated onto a copper foil current collector to obtain a uniform slurry. After drying at 60°C for 2 hours and transferring to a 120°C oven to remove moisture, a Si electrode sheet (Si-slurry electrode) was obtained and used for bending performance testing.

[0090] The CNT@Si, CNT@Si-film, CNT@SiPA, CNT@SiPA-film, CNT@SiPAC, CNT@SiPAC-film, and Si-slurry electrode obtained in Examples 1-3 and Comparative Example 1 were cut into disks with a diameter of 10 mm to obtain flexible electrodes without the need for additional binders and current collectors. Specific capacities were calculated based on the mass of Si.

[0091] To test the performance of the lithium-ion battery anode of this invention, CNT@Si, CNT@SiPA, CNT@SiPAC, CNT@Si-film, CNT@SiPA-film, and CNT@SiPAC-film were used as anodes, lithium foil as cathode, and commercial PP film as separator. 1 mol / L lithium hexafluorophosphate (LiPF6) was added as electrolyte to a non-aqueous solvent of fluoroethylene carbonate (FEC), hydrofluoroether (HFE), and fluoroethyl methyl carbonate (FEMC) in a 2:6:2 mass ratio. Button cells were assembled using CR2025 battery cases. The assembly process of the button cells was carried out entirely in an argon-filled glove box.

[0092] Please see Figure 7 The button cell assembled from the CNT@Si, CNT@Si-film, CNT@SiPAC, and CNT@SiPAC-film anodes in Example 1 was first tested with 0.2Ag. -1 Activation was performed by cycling at a current density of 5 times, and then at 0.4 A g. -1 Cycling is performed at current densities. From Figure 7 As can be seen from the data, the initial specific capacity of the coin cell assembled with the CNT@Si anode is 2453.5 mAh g. -1 After 50 cycles, it only maintained 242.2 mAh g. -1 The CNT@Si film anode exhibited a slightly higher specific capacity than the CNT@Si anode because the cross-laminated SACNT films on both sides mitigated the loss of active material; however, the specific capacity was only 327.9 mAh g after 50 cycles. -1 The coulombic efficiency of CNT@Si and CNT@Si-film anodes is unstable during cycling, possibly because the broken nano-silicon exposes a new interface with the electrolyte and excessively consumes the electrolyte. Figure 7 It can also be seen that the initial specific capacity of the coin cell assembled with CNT@SiPAC anode and CNT@SiPAC-film anode is 2199.5 mAh g. -1 and 2380.4mAh g -1 And after 200 cycles, it maintained 1046.1 mAh g. -1 and 1170.4mAh g -1 Furthermore, the coulombic efficiency remained stable during cycling after high-temperature treatment of the nano-silicon coating. These results indicate that surface coating modification with nano-silicon effectively suppressed capacity decay of the silicon anode.

[0093] Please see Figure 8 This is for using CNT@SiPAC in Examples 1-3. 0.01 - Membrane, CNT@SiPAC 0.005- Membranes and CNT@SiPAC 0.015 - Cycle performance diagram of a coin cell obtained from a membrane anode. Figure 8 As can be seen from this, CNT@SiPAC 0.005 - Membrane, CNT@SiPAC 0.01 - Membrane and CNT@SiPAC 0.015 The initial specific capacities of the membrane anode were 2110.1, 2380.4, and 3357.5 mAh g⁻¹, respectively. At 0.4 A g⁻¹... -1 After 200 cycles, the specific capacities of the three anodes were 735.3, 1170.4, and 916.8 mAh g, respectively. -1 The results show that the CNT@SiPAC in Example 1 0.01 - The membrane exhibits the best cycling performance.

[0094] Please see Figure 9 In the CNT@SiPAC-film anode, the areal loading of Si was 1.19 mg / cm³. -2 1.38mgcm -2 1.72mg cm -2 and 1.99mg cm -2 The cycle capacity curve at that time. (From...) Figure 9 As can be seen, the areal capacities of the first charge-discharge cycle were 2.84, 4.60, 6.92, and 8.34 mAh cm⁻¹, respectively. -2 At 0.4A g -1 After 100 cycles at current densities, the current-to-weight ratios remained at 1.92, 2.45, 2.75, and 2.87 mAh cm⁻¹, respectively. -2 This indicates that the CNT@SiPAC-film anode of the present invention has good cycle performance.

[0095] The above Figure 7-9 Test results show that after coating the surface of nano-silicon with a PANI coating, the composite of nano-silicon and carbon nanotubes is more uniform, improving the uniformity of the anode; moreover, the carbon nanotube functional layer reduces the loss of active material, effectively improving the cycle stability of the CNT@SiPAC-film anode. Simultaneously, high-temperature calcination increases the lithium-ion diffusion coefficient D. Li+ This reduces the contact resistance R1 and the interface charge transfer resistance R. ct The three-dimensional network-like CNT structure provides sufficient electron conduction network and ion diffusion channels, enabling faster reaction kinetics and exhibiting better rate performance.

[0096] Please see Figure 10 At current densities of 0.2, 0.4, 0.8, 2.0, and 4.0 A g -1At that time, the specific capacities of the CNT@SiPAC- membrane anode were 2344.9, 2207, 1849.4, 1539.2 and 1249.7 mAh g, respectively. -1 When the current density changes from 4.0 A / g... -1 Restored to 0.2A g -1 At that time, the discharge specific capacity recovered to 2351.5 mAh g. -1 .Depend on Figure 10 It can also be seen that the capacity of the CNT@SiPAC anode is lower than that of the CNT@SiPAC-film anode, at 0.2 A g. -1 The initial specific capacity at the given current density is 2039.2 mAh g. -1 When from 4.0A g -1 Restored to 0.2A g -1 At that time, the specific capacity of the CNT@SiPAC anode recovered to 1933.1 mAh g. -1 The capacity retention rate was 94.79%, lower than that of the CNT@SiPAC-film anode. This demonstrates the effectiveness of the cross-laminated SACNT film; the carbon nanotube functional layer of the CNT@SiPAC-film anode of this invention can effectively mitigate the loss of active materials. Figure 10 It can also be seen that CNT@Si and CNT@Si-film anodes exhibit poor rate performance at 4.0 A g. -1 At the given current density, the specific capacity is 17.0 mAh g. -1 and 31.1mAh g -1 When the current density recovers to 0.2 A g -1 At that time, the capacity retention of the CNT@Si anode was only 68.36%, and the capacity retention of the CNT@Si-film anode was only 68.54%. This result indicates that rapid alloying / dealloying significantly affects the electrochemical performance of nano-silicon. Figure 10 This demonstrates that the CNT@SiPAC-film anode exhibits the best rate performance, confirming that the PANI coating, carbonization, and carbon nanotube functional layer scheme can achieve rapid reaction kinetics.

[0097] Please see Figure 11 The SiPAC / / Li pouch cell assembled using CNT@SiPAC-film achieved a current density of 0.4 A g. -1 At that time, the capacity after the first cycle was 36.69mAh, and the capacity retention rate after 50 cycles was 86.9%, which shows great commercial potential.

[0098] Please see Figure 12The CNT@SiPAC-film electrode in Example 1 and the Si-slurry electrode in Comparative Example 1 were subjected to long-cycle bending at 90° and 180° using a bending life testing machine, and the normalized resistance changes were measured in real time. Figure 12 As can be seen, the resistance of the CNT@SiPAC-film electrode fluctuates very little over long periods; the resistance increase after 10,000 bends at 90° is 2.66%, and after 10,000 bends at 180° is 3.14%. This indicates that the carbon nanotubes construct a flexible yet robust mechanical framework, enabling the film to withstand long-term bending at large angles. In contrast, the Si-slurry electrode is very intolerant of bending: the resistance increases by 779% after 90° bends and by 994% after 3 bends at 180°, followed by a sharp increase indicating a short circuit. These results demonstrate that the CNT@SiPAC-film electrode of this invention exhibits excellent flexibility and durability compared to conventional electrodes using slurry and metal current collectors.

[0099] Pre-lithiated CNT@SiPAC film anodes and CNT@LFP film cathodes were assembled into a SiPAC / / LFP pouch cell for bending capacity retention testing. (See also...) Figure 13 The SiPAC / / LFP pouch cell exhibited a charging capacity of 60.12 mAh and a discharging capacity of 56.43 mAh during its first charge-discharge cycle. Due to pre-lithiation, the first coulombic efficiency was 93.9%. Subsequently, the pouch cell was bent at 90° 10,000 times. After bending, the pouch cell maintained its appearance intact, with a charging capacity of 57.84 mAh and a discharging capacity of 54.48 mAh. The 96.2% charge capacity retention and 96.5% discharge capacity retention of the SiPAC / / LFP pouch cell strongly demonstrate the excellent flexibility of the CNT@SiPAC film anode.

[0100] This invention provides a method for preparing a flexible nano-silicon anode from both surface modification and structural design perspectives. A positively charged carbonizable polymer is coated onto the nano-silicon surface, improving anode uniformity through a "dispersion anchoring" effect between the positively charged polymer and the negatively charged carbon nanotubes. The amorphous carbon derived from the positively charged polymer addresses technical issues such as severe volume changes in nano-Si during cycling, which can lead to anode cracking and rapid capacity decay, nano-silicon agglomeration, and the poor conductivity and slow electrode kinetics of nano-silicon. With the help of the carbon nanotube functional layer, the CNT@SiPAC-film anode requires no additional binders, conductive agents, or current collectors, resulting in a lighter lithium-ion battery while maintaining the same specific capacity and total capacity. The carbon nanotube film provides sufficient electron transport networks, ion diffusion channels, space for silicon volume expansion, and robust three-dimensional mechanical support. Furthermore, the CNT functional layers on both surfaces of the composite film effectively reduce the shedding of active material from the electrode surface. Furthermore, the nano-Si anodes obtained by this preparation method exhibit excellent flexibility and can be bent at will.

[0101] Please see Figure 14 This invention also provides a lithium-ion battery anode 100. The lithium-ion battery anode 100 includes a three-dimensional carbon nanotube network structure 102, multiple amorphous carbon-coated silicon nanoparticles 104, and two carbon nanotube functional layers 106. The multiple amorphous carbon-coated silicon nanoparticles 104 are uniformly dispersed in the three-dimensional carbon nanotube network structure 102, and adhere to the surface of the carbon nanotubes in the three-dimensional carbon nanotube network structure 102. The two carbon nanotube functional layers 106 are respectively disposed on two opposite surfaces of the three-dimensional carbon nanotube network structure 102. This lithium-ion battery anode 100 is flexible and self-supporting, and can be bent at will. The amorphous carbon is obtained by high-temperature calcination of a positively charged carbonizable polymer in the above-described lithium-ion battery anode preparation method.

[0102] The positively charged carbonizable polymer refers to a polymer with a positive surface zeta potential, which can decompose into amorphous carbon upon high-temperature calcination. For example, the positively charged carbonizable polymer can be polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0103] In this embodiment, the size of the silicon nanoparticles is 20 nanometers to 80 nanometers. Of course, the size of the silicon nanoparticles is not limited to the size in this embodiment, and can also be silicon nanoparticles of other sizes.

[0104] In the lithium-ion battery anode 100, the preferred mass loading of the nano-silicon is 1.2 mg / cm³. -2 Up to 2mg cm -2 .

[0105] The three-dimensional network structure 102 of carbon nanotubes is a flocculent structure. This flocculent structure is not merely the intertwining of carbon nanotubes, but also a porous and fluffy structure. The presence of multiple micropores in the three-dimensional network structure 102 facilitates electrolyte penetration, improving the adsorption and detachment capacity of the lithium-ion battery anode 100 for lithium ions. Furthermore, because these micropores can accommodate lithium ions, the volume of the lithium-ion battery anode 100 in this invention does not significantly increase when used in a lithium-ion battery.

[0106] The carbon nanotube functional layer 106 comprises at least two super-compliant carbon nanotube films stacked together, with the carbon nanotubes in adjacent super-compliant carbon nanotube films intersecting. The intersection angle of the carbon nanotubes in adjacent super-compliant carbon nanotube films is not limited. In this embodiment, the carbon nanotube functional layer 106 comprises 10 super-compliant carbon nanotube films stacked together, with the intersection angle of the carbon nanotubes in adjacent super-compliant carbon nanotube films being 90 degrees.

[0107] The three-dimensional carbon nanotube network structure 102, the nano-silicon particles 104 coated with amorphous carbon, and the carbon nanotube functional layer 106 in this embodiment are all the same as those described in the preparation method of the lithium-ion battery anode, including all the technical features described in the preparation method of the corresponding lithium-ion battery anode, and will not be repeated here.

[0108] Please see Figure 15 Another embodiment of the present invention provides a lithium-ion battery anode 200. The lithium-ion battery anode 200 includes a three-dimensional carbon nanotube network structure 202 and a plurality of positively charged carbonizable polymer-coated silicon nanoparticles 204. The plurality of positively charged polymer-coated silicon nanoparticles 204 are uniformly dispersed in the three-dimensional carbon nanotube network structure 202, and the plurality of positively charged polymer-coated silicon nanoparticles 204 adhere to the surface of the carbon nanotubes in the three-dimensional carbon nanotube network structure 202.

[0109] The positively charged carbonizable polymer refers to a polymer with a positive surface zeta potential, which can decompose into amorphous carbon upon high-temperature calcination. For example, the positively charged carbonizable polymer can be polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0110] In the nano-silicon particles 204 coated with a positively charged carbonizable polymer, the mass percentage of nano-silicon is preferably 40%-50%. In this embodiment, the positively charged carbonizable polymer is polyaniline, and the mass percentage of nano-silicon in the polyaniline-coated nano-silicon is 45.5%.

[0111] The preferred loading of silicon nanoparticles 204 coated with a positively charged carbonizable polymer is 1-5 mg / cm³. -2 If the loading is too low, the silicon anode capacity will be too small; if the loading is too high, the silicon anode volume will change significantly and pulverization will be severe, resulting in poor capacity retention. The loading within this preferred range can balance anode capacity and capacity retention. In this embodiment, the loading of nano-silicon in the polyaniline-coated nano-silicon particles 204 is 3 mg / cm³. -2 .

[0112] The preferred mass ratio of the three-dimensional carbon nanotube network structure 202 to the nano-silicon particles 204 coated with a positively charged carbonizable polymer is 1:2 to 1:4. In this embodiment, the mass ratio of the carbon nanotubes to the nano-silicon particles coated with polyaniline is 1:3.

[0113] In this embodiment, the size of the silicon nanoparticles is 20 nanometers to 80 nanometers. Of course, the size of the silicon nanoparticles is not limited to the size in this embodiment, and can also be silicon nanoparticles of other sizes.

[0114] The three-dimensional network structure 202 of carbon nanotubes is a flocculent structure. This flocculent structure is not merely the intertwining of carbon nanotubes, but also a porous and fluffy structure. The presence of multiple micropores in the three-dimensional network structure 202 facilitates electrolyte penetration, improving the adsorption and detachment capacity of the lithium-ion battery anode 200 for lithium ions. Furthermore, because these micropores can accommodate lithium ions, the volume of the lithium-ion battery anode 200 in this invention does not significantly increase when used in a lithium-ion battery.

[0115] The lithium-ion battery anode 200 is flexible and self-supporting, and can be bent at will.

[0116] The lithium-ion battery anode 200 may further include two carbon nanotube functional layers (not shown), respectively disposed on two opposite surfaces of the three-dimensional carbon nanotube network structure 202. Each carbon nanotube functional layer comprises at least two super-aligned carbon nanotube films stacked together, with the carbon nanotubes in adjacent super-aligned carbon nanotube films intersecting. In this embodiment, the carbon nanotube functional layer comprises 10 super-aligned carbon nanotube films stacked together, with the intersection angle of the carbon nanotubes in adjacent super-aligned carbon nanotube films being 90 degrees.

[0117] In this embodiment, the three-dimensional carbon nanotube network structure 202, which is coated with positively charged carbonizable polymer nanoparticles 204 and two carbon nanotube functional layers, and the positively charged carbonizable polymer are the same as those described in the preparation method of the lithium-ion battery anode, including all the technical features described in the preparation method of the corresponding lithium-ion battery anode, will not be repeated here.

[0118] The lithium-ion battery anode prepared using the method provided in this invention exhibits high uniformity. Positively charged, carbonizable polymer-derived amorphous carbon can address technical issues such as severe volume changes in nano-Si during cycling, which can lead to anode cracking and rapid capacity decay, agglomeration of nano-silicon, poor conductivity of nano-silicon, and slow electrode kinetics. With the aid of carbon nanotube functional layers, the lithium-ion battery anode requires no additional binders or current collectors, saving energy and further reducing the anode's volume and weight. The three-dimensional network structure of carbon nanotubes provides sufficient electron transport networks, ion diffusion channels, space reserved for silicon volume expansion, and robust three-dimensional mechanical support. Furthermore, the CNT functional layers on both surfaces of the composite film effectively reduce the shedding of active material from the electrode surface. In addition, this lithium-ion battery anode exhibits excellent flexibility. Because multiple micropores exist in both the three-dimensional network structure and the carbon nanotube functional layers, the adsorption and deintercalation capabilities of the lithium-ion battery anode are improved. Moreover, since these micropores can accommodate lithium ions, the volume of the lithium-ion battery in this invention does not significantly increase during use.

[0119] Furthermore, those skilled in the art may make other changes within the spirit of this invention. Of course, all such changes made in accordance with the spirit of this invention should be included within the scope of protection claimed by this invention.

Claims

1. A method for preparing a lithium-ion battery anode, characterized in that, Includes the following steps: Step S1: Provide a nano-silicon material and perform amino grafting on the nano-silicon material to obtain a nano-silicon material with amino grafted on the surface. Coat the surface of the nano-silicon material with amino grafted on the surface with a positively charged carbonizable polymer to obtain nano-silicon with a positively charged carbonizable polymer coated on the surface. Step S2: Provide a solvent and carbon nanotubes, wherein the mass ratio of the carbon nanotubes to the nano-silicon coated with a positively charged carbonizable polymer is 1:2-1:

4. Add the carbon nanotubes and the nano-silicon coated with a positively charged carbonizable polymer to the solvent in a certain proportion and perform ultrasonic dispersion to obtain a dispersion. Step S3: Vacuum filter the dispersion to obtain a composite film of carbon nanotubes and nano-silicon coated with a positively charged carbonizable polymer. Step S4: A carbon nanotube functional layer is deposited on each of the two opposite surfaces of the composite membrane. The carbon nanotube functional layer comprises at least two super-aligned carbon nanotube membranes stacked together. as well as Step S5: The composite film with carbon nanotube functional layers laid in step S4 is subjected to high-temperature calcination, so that the positively charged carbonizable polymer in the composite film is carbonized into amorphous carbon.

2. The method for preparing the lithium-ion battery anode as described in claim 1, characterized in that, In the at least two super-aligned carbon nanotube films, the carbon nanotubes in adjacent super-aligned carbon nanotube films are arranged perpendicularly and cross each other.

3. The method for preparing the lithium-ion battery anode as described in claim 1, characterized in that, The positively charged carbonizable polymer is polyaniline.

4. The method for preparing the lithium-ion battery anode as described in claim 1, characterized in that, The size of the silicon nanoparticles is 20 nanometers to 80 nanometers.

5. The method for preparing a lithium-ion battery anode as described in claim 1, characterized in that, In step S2, the carbon nanotubes are scraped directly from a super-aligned carbon nanotube array into the solvent.

6. The method for preparing a lithium-ion battery anode as described in claim 1, characterized in that, In step S2, after ultrasonic dispersion, the carbon nanotubes form a three-dimensional network structure in the solvent, and the nano-silicon coated with a positively charged carbonizable polymer adheres to the surface of the carbon nanotubes forming the three-dimensional network structure.

Citation Information

Patent Citations

  • Carbon nano pipe rpoe and preparation method thereof

    CN100411979C

  • Method for making thin film lithium ion battery

    US20140013588A1

  • Li-ion battery electrodes having nanoparticles in a conductive polymer matrix

    US20140045065A1